LanB1 Cooperates With Kon-Tiki During Embryonic Muscle Migration in Drosophila - Pérez-Moreno, Juan José; Santa-Cruz Mateos, Carmen; Martín-Bermudo, María Dolores; Estrada, Beatriz (Frontiers in Cell and Developmental Biology, 2022)
Muscle development is a multistep process that involves cell specification, myoblast fusion, myotube migration, and attachment to the tendons. In spite of great efforts trying to understand the basis of these events, little is known about the molecular mechanisms underlying myotube migration. Knowledge of the few molecular cues that guide this migration comes mainly from studies in Drosophila. The migratory process of Drosophila embryonic muscles involves a first phase of migration, where muscle progenitors migrate relative to each other, and a second phase, where myotubes migrate searching for their future attachment sites. During this phase, myotubes form extensive filopodia at their ends oriented preferentially toward their attachment sites. This myotube migration and the subsequent muscle attachment establishment are regulated by cell adhesion receptors, such as the conserved proteoglycan Kon-tiki/Perdido. Laminins have been shown to regulate the migratory behavior of many cell populations, but their role in myotube migration remains largely unexplored. Here, we show that laminins, previously implicated in muscle attachment, are indeed required for muscle migration to tendon cells. Furthermore, we find that laminins genetically interact with kon-tiki/perdido to control both myotube migration and attachment. All together, our results uncover a new role for the interaction between laminins and Kon-tiki/Perdido during Drosophila myogenesis. The identification of new players and molecular interactions underlying myotube migration broadens our understanding of muscle development and disease.